Epicardial, pericardial and total cardiac fat and cardiovascular disease in type 2 diabetic patients with elevated urinary albumin excretion rate. (September 2017) - Christensen, Regitse H; von Scholten, Bernt J; Hansen, Christian S; Heywood, Sarah E; Rosenmeier, Jaya B; Andersen, Ulrik B; Hovind, Peter; Reinhard, Henrik; Parving, Hans-Henrik; Pedersen, Bente K; Jørgensen, Marit E; Jacobsen, Peter K; et al.
Background: We evaluated the association of cardiac adipose tissue including epicardial adipose tissue and pericardial adipose tissue with incident cardiovascular disease and mortality, coronary artery calcium, carotid intima media thickness and inflammatory markers. Design: A prospective study of 200 patients with type 2 diabetes and elevated urinary albumin excretion rate (UAER). Methods: Cardiac adipose tissue was measured from baseline echocardiography. The composite endpoint comprised incident cardiovascular disease and all-cause mortality. Coronary artery calcium, carotid intima media thickness and inflammatory markers were measured at baseline. Cardiac adipose tissue was investigated as continuous and binary variable. Analyses were performed unadjusted (model 1), and adjusted for age, sex (model 2), body mass index, low-density lipoprotein cholesterol, smoking, glycated haemoglobin, and systolic blood pressure (model 3). Results: Patients were followed-up after 6.1 years for non-fatal cardiovascular disease ( n = 29) or mortality ( n = 23). Cardiac adipose tissue ( p = 0.049) and epicardial adipose tissue ( p = 0.029) were associated with cardiovascular disease and mortality in model 1. When split by the median, patients with high cardiac adipose tissue had a higher risk of cardiovascular disease and mortality than patients with low cardiac adipose tissue in unadjusted (hazard ratio 1.9, confidence interval: 1.1; 3.4, p = 0.027) and adjusted (hazard ratio 2.0, confidence interval: 1.1; 3.7, p = 0.017) models. Cardiac adipose tissue ( p = 0.033) was associated with baseline coronary artery calcium (model 1) and interleukin-8 (models 1–3, all p < 0.039). Conclusions: In type 2 diabetes patients without coronary artery disease, high cardiac adipose tissue levels were associated with increased risk of incident cardiovascular disease or all-cause mortality even after accounting for traditional cardiovascular disease risk factors. High cardiac adipose tissue amounts were associated with subclinical atherosclerosis (coronary artery calcium) and with the pro-atherogenic inflammatory marker interleukin-8.